Role of diagnostic hystero-laparoscopy in the evaluation of infertility: A retrospective study of 300 patients - Prasanta K Nayak; Purna C Mahapatra; J J Mallick; S Swain; Subarna Mitra; Jayaprakash Sahoo (Wolters Kluwer Medknow Publications, 2013)
Objective: To determine the role of diagnostic hysterolaparoscopy in the evaluation of infertility in tertiary care centres. Materials and Methods: This retrospective study was conducted at two tertiary care centres (the infertility clinics of Sriram Chandra Bhanj Medical College and Prachi hospital at Cuttack, Odisha) throughout the year in 2008. Women aged 20-40 years with normal hormone profile without male factor infertility were included. Results: Out of 300 cases, 206 (69%) patients had primary infertility. While laparoscopy detected abnormalities in 34% of the cases, significant hysteroscopy findings were noted in 18% of cases. Together, diagnostic hysterolaparoscopy detected abnormalities in 26% of the infertile patients in both groups. While the most common laparoscopic abnormality was endometriosis (14%) and adnexal adhesion (12%) in primary and secondary infertile patients, respectively, hysteroscopy found intrauterine septum as the most common abnormality in both groups. Conclusions: Hysterolaparoscopy is an effective diagnostic tool for evaluation of certain significant and correctable tubo-peritoneal and intrauterine pathologies like peritoneal endometriosis, adnexal adhesions, and subseptate uterus, which are usually missed by other imaging modalities.